Liquisolid ibuprofen tablets - Lannie Hadisoewignyo; Evania hadi; Nehru Wibowo (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Ibuprofen is an antiinflamatory drugs with poor solubility in water but good permeability in the gastrointestinal tract. Liquisolid tablet is the one method of increasing solubility and dissolution rate of ibuprofen. The aims of this study was to determine the effect of glycerine and propylene glicol as non volatile solvent and PVP K-30 as hydrophilic polymer on the dissolution rate of liquisolid ibuprofen tablets. In this research, there are 7 formulas of liquisolid ibuprofen tablets were made. The ratio of ibuprofenin glycerine is 1 : 3 and of propilene glicol is 5:1 with various concentration of PVP K-30 (5, 10, and 15%). Formula I was made as a control so there was no addition of non volatile solvent and hydrophilic polymer. Based on the results, liquisolid ibuprofen tablets using glycerine or propylene glycol as a non volatile solvent and PVP K-30 as a hydrophilic polymer can increase the dissolution rate constant of liquisolidibuprofen tablets comparedthat of ibuprofen conventional tablets (non liquisolid). The addition of PVP K-30 as a hydrophilic polymer can increase the dissolution rate constants liquisolid ibuprofen tablets until a concentration of more than 10% because the polymer will swell and form a viscous layer that inhibits the disintegration so that the percent release decrease.Key words:Ibuprofen, liquisolid, non volatile solvent, hydrophilic polymer.